Graphene-Au nanoparticle based vertical heterostructures: A novel route towards high-ZT Thermoelectric devices. (August 2017) - Juang, Zhen-Yu; Tseng, Chien-Chih; Shi, Yumeng; Hsieh, Wen-Pin; Ryuzaki, Sou; Saito, Noboru; Hsiung, Chia-En; Chang, Wen-Hao; Hernandez, Yenny; Han, Yu; Tamada, Kaoru; Li, Lain-Jong
Abstract: Monolayer graphene exhibits impressive in-plane thermal conductivity (> 1000 W m –1  K –1 ). However, the out-of-plane thermal transport is limited due to the weak van der Waals interaction, indicating the possibility of constructing a vertical thermoelectric (TE) device. Here, we propose a cross-plane TE device based on the vertical heterostructures of few-layer graphene and gold nanoparticles (AuNPs) on Si substrates, where the incorporation of AuNPs further inhibits the phonon transport and enhances the electrical conductivity along vertical direction. A measurable Seebeck voltage is produced vertically between top graphene and bottom Si when the device is put on a hot surface and the figure of merit ZT is estimated as 1 at room temperature from the transient Harman method. The polarity of the output voltage is determined by the carrier polarity of the substrate. The device concept is also applicable to a flexible and transparent substrate as demonstrated. Graphical abstract: Highlights: A new TE device of few-layer graphene with intercalated Au nanoparticles. The ueage of Au nanoparticles enhances the cross-plane electrical conductivity. The figure of merit ZT is estimated as 1 at room temperature. The polarity of output voltage is determined by the carrier polarity of the substrate. The device concept is applicable to a flexible and transparent substrate.